Extended Cleavage Specificity of Human Neutrophil Elastase, Human Proteinase 3, and Their Distant Ortholog Clawed Frog PR3—Three Elastases With Similar Primary but Different Extended Specificities and Stability - Fu, Zhirong; Thorpe, Michael; Akula, Srinivas; Chahal, Gurdeep; Hellman, Lars T. (Frontiers in Immunology, 2018)
Serine proteases are major granule constituents of several of the human hematopoietic cell lineages. Four proteolytically active such proteases have been identified in human neutrophils: cathepsin G (hCG), N-elastase (hNE), proteinase 3 (hPR-3) and neutrophil serine protease 4 (hNSP-4). Here we present the extended cleavage specificity of two of the most potent and most abundant of these enzymes, hNE and hPR-3. Their extended specificities were determined by phage display and by the analysis of a panel of chromogenic and recombinant substrates. hNE is an elastase with a relatively broad specificity showing a preference for regions containing several aliphatic amino acids. The protease shows self-cleaving activity, which results in the loss of activity during storage even at +4oC. Here we also present the extended cleavage specificity of hPR-3. Compared with hNE, it shows considerably lower proteolytic activity. However, it is very stable, shows no self-cleaving activity and is actually more active in the presence of SDS, possibly by enhancing the accessibility of the target substrate. This enables specific analysis of hPR-3 activity even in the presence of all the other neutrophil enzymes with addition of 1 % SDS. Neutrophils are the most abundant white blood cell in humans and one of the key players in our innate immune defence. The neutrophil serine proteases are very important for the function of the neutrophils and therefore also interesting from an evolutionary perspective. In order to study the origin and functional conservation of these neutrophil proteases we have identified and cloned an amphibian orthologue, Xenopus PR-3 (xPR-3). This enzyme was found to have a specificity very similar to hPR-3 but did not show the high stability in the presence of SDS. The presence of an elastase in Xenopus closely related to hPR-3 indicates a relatively early appearance of these enzymes during vertebrate evolution.